2021
DOI: 10.1097/med.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Applying implementation science to improve care for familial hypercholesterolemia

Abstract: Purpose of reviewImproving care of individuals with familial hypercholesteremia (FH) is reliant on the synthesis of evidence-based guidelines and their subsequent implementation into clinical care. This review describes implementation strategies, defined as methods to improve translation of evidence into FH care, that have been mapped to strategies from the Expert Recommendations for Implementing Change (ERIC) compilation.Recent findingsA search using the term ‘familial hypercholesterolemia’ returned 1350 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The application of principles from implementation science to the field of FH has been discussed in many recent articles including original research, reviews, commentaries, and guidelines (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). By leveraging implementation science, which aims to close the large gap from knowledge generation to implementation into practice, we can improve every component of FH care.…”
Section: Discussionmentioning
confidence: 99%
“…The application of principles from implementation science to the field of FH has been discussed in many recent articles including original research, reviews, commentaries, and guidelines (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). By leveraging implementation science, which aims to close the large gap from knowledge generation to implementation into practice, we can improve every component of FH care.…”
Section: Discussionmentioning
confidence: 99%
“…23 Clinician and patient knowledge related to FH impacts care from identification to treatment. [24][25][26][27] Once identified, access to treatment can be difficult. Low prescribing of PCSK9 inhibitors due to access problems is consistent with a large cohort study conducted by the Family Heart Foundation (previously the FH Foundation).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors noted that future work should be focused on thoroughly defining these implementation strategies with over half missing the temporality and dose of these strategies so that they could be replicated in future studies [27 ▪ ]. The other review article, which focused on 37 studies for improving care for individuals with familial hypercholesterolemia, mapped the implementation strategies used [28 ▪ ]. The implementation strategies included assess for readiness, identify barriers and facilitators, develop and organize quality monitoring systems, create new clinical teams, facilitate relay of clinical data to providers, and involve patients and family members [28 ▪ ].…”
Section: Implementation Science As a Solution To Improve Carementioning
confidence: 99%
“…The other review article, which focused on 37 studies for improving care for individuals with familial hypercholesterolemia, mapped the implementation strategies used [28 ▪ ]. The implementation strategies included assess for readiness, identify barriers and facilitators, develop and organize quality monitoring systems, create new clinical teams, facilitate relay of clinical data to providers, and involve patients and family members [28 ▪ ]. This review found that 22% of the studies used an implementation science theory, model, or framework to conduct their analysis [28 ▪ ].…”
Section: Implementation Science As a Solution To Improve Carementioning
confidence: 99%